2021
DOI: 10.1088/1361-665x/ac1908
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of NiTi stents with open-cell and variable diameter

Abstract: This work investigates the processing of NiTi open-cells peripheral stents with variable diameter by SLM and consecutive heat treatments. The production of open-cell designs via SLM requires dedicated processing strategies to avoid the use of support structures with comparable dimensions to the stent struts. Process parameters were studied with an SLM system operating with pulsed wave emission to assess the geometrical fidelity and the density of thin struts. The novel stent mesh was designed and produced empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…The inherent layering effect can be clearly observed in Figure 11 c. Since the SAFs were manufactured on the edge of resolution such layering effect is inevitable. Besides, fused particles on the SAF surface are presented that are common surface defects [ 20 ], but considering synthesized object dimensions these defects become more influential. Both surface irregularities (layering and fused particles) possibly can be removed by chemical etching [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inherent layering effect can be clearly observed in Figure 11 c. Since the SAFs were manufactured on the edge of resolution such layering effect is inevitable. Besides, fused particles on the SAF surface are presented that are common surface defects [ 20 ], but considering synthesized object dimensions these defects become more influential. Both surface irregularities (layering and fused particles) possibly can be removed by chemical etching [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the absence of research dedicated to the manufacturing of NiTi Self-Adjusting Files by LPBF technology, it is worth mentioning alternative micro-scale devices that received increased attention. Several works were dedicated to the investigation of the feasibility of printing stents for coronary vessels from Co-Cr [ 18 ], titanium [ 11 ], steel [ 19 ], and NiTi [ 20 ], which previously were made using laser cutting methods from hollow tubes [ 21 ]. It was demonstrated that resolution, surface finish, and layer bonding dramatically impact the stent performance [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are numerous existing and ongoing studies on the fabrication of SMA components using AM techniques, with a lot of interest given toward its potential in the medical sector. 48,115,116,[118][119][120][121]125,164,165 Maffia et al 166 have investigated the application of SLM for the fabrication of customizable NiTi stents, assessing it to be able to fabricate NiTi open-cell peripheral stents of good geometrical fidelity and high density. Recently, the vivo biocompatibility of load-bearing and load-sharing NiTi implants fabricated through SLM was investigated by Naujokat et al, 167 producing promising results.…”
Section: Current and Future Prospectsmentioning
confidence: 99%
“…One of the most widespread AM techniques for metals is the Laser Powder Bed Fusion (LPBF), which uses a high-power laser beam to melt locally a layer-wise deposited metallic powder. The recent literature is rich of research works focused on the 4D printing of NiTi, in particular using LPBF [21][22][23][24][25][26][27][28][29][30][31][32][33], showing the interest of the scientific community on this topic, as also evidenced by a substantial number of reviews [13,14,34].…”
Section: Introductionmentioning
confidence: 99%